An outline of Knowledge Management - Rozenberg, Magdalena (Glottodidactica, 2017)
Knowledge management is the concept concerning the question how to use knowledge in the most efficient way within an organization and creating and managing new knowledge which allows for improving efficiency of a modern organization. The author of the article has made an attempt to clearly present the concept of knowledge management. She has described and defined its main presumptions and has made use of economic science in order to explain how management is understood in economy. Finally the author has posed the question of the meaning of knowledge management in the process of a foreign language teaching and learning.